Colon cancer-specific antigen-2 may be used as a detecting and prognostic marker in colorectal cancer: a preliminary observation. - Gang Xue; Xiaojuan Wang; Yong Yang; Degui Liu; Ying Cheng; Jun Zhou; Yongkuan Cao (PLoS ONE, 2014)
Background A specific and sensitive serum marker for colorectal cancer (CRC) detection and surveillance is central to effective treatment. It was preliminarily reported that some nuclear matrix proteins may be served as a specific blood based marker for colon cancer. The objective of this study is to evaluate the value of serum CCSA-2 detection in diagnosis, prognostic estimation and surveillance for CRC. Method Serum CCSA-2 protein was measured in 181 various patient populations and 20 healthy donors before surgery. For 106 CRC patients, it was also measured on day 7 after surgery. Among them, 49 CRC patients' CCSA-2 protein were measured during the follow-up period according to NCCN Guideline. Results The serum CCSA-2 concentration in CRC patients was significantly higher than which in other patients and healthy individuals. Serum CCSA-2, at the cut-off point of 64.10 ng/mL, had a sensitivity of 98.10% and a specificity of 97.90% in separating CRC populations from all other individuals. The CCSA-2 assay was significantly more sensitive than CEA and CA19-9 assay in CRC detection. After surgery, the serum CCSA-2 level of CRC patients declined significantly, but it rebounded to a high level when recurrences occurred. The pre-operative serum CCSA-2 level in patients who had a relapse within the follow-up period was significantly higher than which in patients without relapse. Conclusions Serum CCSA-2 not only may be a potential biomarker using in screening and surveillance of CRC, but also may be an independent prognostic marker for CRC patients. Further clinical trials need to be performed in a larger population of patients to ulteriorly confirm these results.